Research Progress of Exosomes in Bone Diseases: Mechanism, Diagnosis and Therapy - Meng, Fanying; Xue, Xu; Yin, Zhifeng; Gao, Fei; Wang, Xiuhui; Geng, Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
With the global escalation of the aging process, the number of patients with bone diseases is increasing year by year. Currently, there are limited effective treatments for bone diseases. Exosome, as a vital medium in cell-cell communication, can mediate tissue metabolism through the paracrine transmission of various cargos (proteins, nucleic acids, lipids, etc.) carried by itself. Recently, an increasing number of researchers have proven that exosomes play essential roles in the formation, metabolism, and pathological changes of bone and cartilage. Because exosomes have the advantages of small size, rich sources, and low immunogenicity, they can be used not only as substitutes for the traditional treatment of bone diseases, but also as biomarkers for the diagnosis of bone diseases. This paper reviews the research progress of several kinds of cells derived-exosomes in bone diseases and provides a theoretical basis for further research and clinical application of exosomes in bone diseases in the future.